Osservazioni sul concetto di oggetto della psicologia Remarks on the concept of object of psychology - Richard Avenarius (Scuola delle Scienze Umane e Sociali. Quaderni, 2017)
Remarks on the concept of object of psychology is Richard Avenarius last work and it represents his attempt to establish the fledgling scientific, physiological, experimental psychology on rigorous philosophical basis. With this work the founder of the so-called Empiriocriticism participates to the wide debate on the definition of psychology, along with notable personalities of the time, such as Wilhelm Wundt, Ernst Mach, Oswald Külpe, Hermann Ebbinghaus, Hugo Münsterberg and Edward B. Titchener.